(untitled) (Research, Society and Development, 2021)
The pedagogy that Paulo Freire built throughout his work transformed the view of Brazilian education. The educator has developed a liberating and problematizing pedagogy that is, at the same time, inclusive and understands the differences and heterogeneity of education, including the population of learners who have Attention Deficit Hyperactivity Disorder as well as Oppositional Defiant Disorder. Aiming to analyze the inclusive pedagogy of Freire, the ADHD and the TOD, the methodology used was exploratory bibliographical research with a qualitative character. A textual analysis was carried out seeking common, comparative and correlational points between the themes addressed. The main results found were the verification of the inclusive character of Freire’s pedagogy, in the approach to disorders, the relationship between ADHD and ODD. Both these and the discussions were presented together, under four headings, and the conclusions presented in the closing remarks.